“Digital marketing as a tool to enhance the competitiveness of the enterprise” - Malinko, Yuliia (2025)
With the rapid development of the global network, traditional approaches to enterprise management, particularly its marketing activities, are evolving. The use of the Internet now encompasses virtually all aspects of the marketing activities of many companies (Lorvi & Voitovych, 2021, p. 5). Traditional marketing tools are becoming more effective through their integration into digital platforms. The distinctive innovative capabilities of the digital environment have shaped a new marketing paradigm known as digital marketing. The overall marketing mix should be considered from the perspective of its application in the online environment. Therefore, researching digital marketing tools and strategies becomes an extremely important aspect for the development of enterprises. This qualification paper aims to provide a systematic analysis of the digital marketing strategy of Private Joint-Stock Company "Edelvika". Specifically, it seeks to identify the key success factors and shortcomings in the use of digital marketing and to formulate recommendations for optimising marketing performance and enhancing competitiveness through online instruments. This research focuses on digital marketing tools and their impact on the marketing activities and competitiveness of PJSC "Edelvika". The results of the analysis showed that the implementation of digital marketing tools, particularly social media, content marketing, SEO optimisation and targeted advertising, contributed to an increase in brand awareness and consumer engagement online. However, several challenges were identified, including the uneven distribution of the advertising budget and the limited use of analytical tools. Based on the findings, a set of recommendations was formulated to optimise PJSC "Edelvika’s" digital marketing strategy, with the aim of improving the efficiency of online communications and strengthening the company’s competitive position in the market. This qualification paper systematises the theoretical and methodological foundations of digital marketing as a tool for improving marketing performance and competitiveness. It also examines the specific features of PJSC "Edelvika’s" marketing activities and substantiates the company’s choice of digital marketing strategy.